Imaging Intra-abdominal Burkitt's Lymphoma: From Discrete Bowel Wall Thickening to Diffuse Soft Tissue Infiltration. Issue 3 (August 2017) - Harris, Alison C.; MacLean, Kelly A.; Grunau, Gilat L.; Chang, Silvia D.; Martin, Nancy
Burkitt's lymphoma is a highly aggressive non-Hodgkin's B-cell lymphoma, which often presents with intra-abdominal involvement. The purpose of this pictorial review is to illustrate the various intra-abdominal imaging findings of Burkitt's lymphoma. Extranodal disease at presentation is common, including involvement of the bowel, stomach, pancreas, spleen, and mesentery.